Digital competencies in management: a way to superior competitiveness and resistance to changes - Gerasimenko, Valentina Vasilievna; Razumova, Tatyana Olegovna (Serbian Journal of Management, 2020)
Digital technologies in management of companies are becoming a necessary condition for their competitiveness. The use of these technologies requires changes in management processes and in the organization of managers’ work. The authors have looked into the usage of digital technologies and problems which Russian managers face when dealing with them, and into the attitudes to digital technologies that reveal the existing challenges, including the resistance to the oncoming changes. The paper analyzes the issues related to the ways of building new managerial competences in digital economy.